2014
DOI: 10.1007/s10620-014-3205-4
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Serum and Ascitic Fluid C-Reactive Protein in Differential Diagnosis of Benign and Malignant Ascites

Abstract: Increased levels of serum and ascitic fluid CRP were associated with malignant ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The high levels of C-reactive protein and insulin-like growth factor-1 in ascitic fluid make it possible to suspect malignant ascites[28], and a cholesterol level of more than 45 mg/100 mL in combination with cytology and carcinoembryonic antigen determination have diagnostic value[29]. Malignant ascites can also be assumed if there is a high level of C-reactive protein both in ascitic fluid and blood serum[30].…”
Section: Ascitic Fluid Analysismentioning
confidence: 99%
“…The high levels of C-reactive protein and insulin-like growth factor-1 in ascitic fluid make it possible to suspect malignant ascites[28], and a cholesterol level of more than 45 mg/100 mL in combination with cytology and carcinoembryonic antigen determination have diagnostic value[29]. Malignant ascites can also be assumed if there is a high level of C-reactive protein both in ascitic fluid and blood serum[30].…”
Section: Ascitic Fluid Analysismentioning
confidence: 99%
“…At a cut-off value of 7.3 ng/ml, serum CRP levels had specificity of 77.3% and sensitivity of 84.7% for detecting malignant ascites respectively. Similarly, Yuskel et al, 19 also showed that mean baseline serum and ascites levels of CRP were significantly higher in Group 2 (low gradient ascites) compared to those in Group 1(high gradient ascites) (p = 0.021, p = <0.0001, respectively).…”
Section: Discussionmentioning
confidence: 70%
“…There was a notable difference between pleural and ascitic effusions in group B, the prevalence of malignant effusions in pleural (20, 23) described previously was lower than we found in the present study for peritoneal effusions, since ascitic effusions were more likely to be malignant. Higher concentrations of CRP have been described in peritonitis (15,16) but also in malignant ascites (25,26). Some ovarian, pancreatic and colonic cancer may have an important inflammatory component.…”
Section: Discussionmentioning
confidence: 99%